2015
DOI: 10.4103/0975-1475.172441
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of age based on tooth cementum annulations: A comparative study using light, polarized, and phase contrast microscopy

Abstract: Context:The identification of living or deceased persons using unique traits and characteristics of the teeth and jaws is a cornerstone of forensic science. Teeth have been used to estimate age both in the young and old, as well as in the living and dead. Gradual structural changes in teeth throughout life are the basis for age estimation. Tooth cementum annulation (TCA) is a microscopic method for the determination of an individual's age based on the analysis of incremental lines of cementum.Aim:To compare ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
2
14
1
1
Order By: Relevance
“…It should be noted that, despite the current literature shows the existence of advanced technologies such as three-dimensional (3D) records of palatal roughness 18 , microscopic analysis of incremental lines of dental cement 19 and the use of softwares for morphometric measurements of dental pulps 20 , and a careful forensic dental examination associated with previous data in dental records, are sufficient to contemplate, with precision and rapidity, the success of the identification procedures, without need of further tests for human identification 13 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that, despite the current literature shows the existence of advanced technologies such as three-dimensional (3D) records of palatal roughness 18 , microscopic analysis of incremental lines of dental cement 19 and the use of softwares for morphometric measurements of dental pulps 20 , and a careful forensic dental examination associated with previous data in dental records, are sufficient to contemplate, with precision and rapidity, the success of the identification procedures, without need of further tests for human identification 13 .…”
Section: Resultsmentioning
confidence: 99%
“…determined that incremental lines of cementum were most clearly visible under a phase-contrast microscope and subsequently under polarized microscope and light microscope. [11] Analysts determined the obserever error and tooth variability in this technique for age estimation and concluded that premolars are the preferred tooth with least interobserver error. Also, by increasing the number of slides per tooth, tooth variance can be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inference of dental age has high reliability and unique significance in individual recognition (Someda et al, 2009;Aboshi et al, 2010;Tardivo et al, 2011). With age, secondary dentin and reparative dentin continue to deposit, so many scholars select secondary dentin deposition as an age-related research indicator, but this study can only be carried out on the corpse (Bommannavar & Kulkarni, 2015;Chopra et al, 2015;Kaur, et al, 2015;Klumb et al, 2016). To make up for this limitation, on the basis of previous studies, we used oral and craniofacial CT to take three-dimensional (3D) images of maxillary canines, selected the ratio of pulp volume (PV) to tooth volume (TV) (PV/ TV) as an indicator to infer individual age, and deduced the equation of related function for individual age inference by using 3D method so as to provide theoretical guidance for the follow-up clinical work of forensic medicine.…”
Section: Introductionmentioning
confidence: 98%